Metformin improves polycystic ovary syndrome in mice by inhibiting ovarian ferroptosis - Peng, Qingjie; Chen, Xiaojiang; Liang, Xiaoxia; Ouyang, Jiahui; Wang, Qiangqiang; Ren, Shuai; Xie, Haibo; Wang, Chunhong; Sun, Yaqun; Wu, Xin; Liu, Hetao; Hei, Changchun; et al. (Frontiers in Endocrinology, 2023)
Background and objective:PCOS is a common metabolic disorder in women of reproductive age, which pathogenesis is very complex. The role of ferroptosis in PCOS is a novel finding, and the mechanistic studies are not clear. Metformin is a commonly used drug of PCOS but few studies on whether metformin can improve the follicle development and ovarian function in PCOS. We aims to use PCOS mouse model to study the effect of metformin on PCOS based on the ovarian function and explored the regulation of metformin in PCOS mice by intervening in ferroptosis pathway. Materials and methods:C57 BL/6J female mice aged 4-5 weeks were purchased and gavaged with letrozole (1 mg/kg/day) combined with high-fat diet for 21days to establish PCOS model, and control group was set up. After modeling, the mice were divided into PCOS model group and metformin treatment group (Met) (n=6).The Met group were gavaged metformin (200 mg/kg/day) for 28 days. The body weight, estrous cycle, glucose tolerance test (OGTT)and insulin resistance test (ITT) were monitored . Then , The mice were euthanized to collect serum and ovaries . Elisa was used to detect changes in related serum hormones (E2, LH, FSH, TP). Ovaries used for molecular biology experiments to detect changes in GPX4, SIRT3, AMPK/p-AMPK, and mTOR/p-mTOR by Western blot and qPCR. Results:Compared with the model group mice, body weight was significantly reduced, and their estrous cycle was restored in Met group. The results of OGTT and ITT showed an improvment of glucose tolerance and insulin resistance . Morphological results showed that after metformin treatment, polycystic lesions in ovaries were reduced, the ovarian function was restored, and the expressions of SIRT3 and GPX4 were elevated. WB results demonstrated that the expressions of p-mTOR and p-AMPK in ovaries were significantly reduced in Model group , but reversed in MET group. Conclusion: Our study confirmed metformin could not only improve body weight and metabolism disorders, but also improve ovarian dysfunction in PCOS mice.In addition, we explored metformin could regulate ferroptosis to improve PCOS via the SIRT3/AMPK/mTOR pathway. Our study complements the mechanisms by which metformin improves PCOS.